ETHNOPHYSICAL STUDIES ON SALAI JIN DANCE IN NORTH MALUKU AS A SOURCE OF LEARNING PHYSICS - Irnin Agustina Dwi Astuti; Ria Asep Sumarni; Irawan Setiadi; Alvina Damayanti (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2022)
Culture in Indonesia is very diverse, ranging from traditional musical instruments, traditional games, regional dance arts, and many others. As an effort to introduce Indonesian culture to students, one of them is by implementing it into the learning process. Therefore, this study connects physics material into local culture in Indonesia, one of which is the Salai Jin Dance in North Maluku. This study aims to examine the concept of physics in the Salai Jin dance. The research method used is descriptive qualitative with data collection techniques through observation, questionnaires and interviews. The data obtained is then analyzed, verified, and reduced then constructed into scientific knowledge and interpreted into physics concepts in physics learning. In this Salai Jin dance, there are various concepts of physics, one of which is the concept of motion, torque, and waves in the material for class X and XI SMA/MA. The results showed that the salai jin dance can be used as a source of learning physics on motion material in class X SMA/MA, and moments of inertia, as well as waves in class XI SMA/MA.